2015
DOI: 10.1016/j.cognition.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Rhetorical features facilitate prosodic processing while handicapping ease of semantic comprehension

Abstract: Studies on rhetorical features of language have reported both enhancing and adverse effects on ease of processing. We hypothesized that two explanations may account for these inconclusive findings. First, the respective gains and losses in ease of processing may apply to different dimensions of language processing (specifically, prosodic and semantic processing) and different types of fluency (perceptual vs. conceptual) and may well allow for an integration into a more comprehensive framework. Second, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 60 publications
10
75
0
1
Order By: Relevance
“…This reading behavior is in line with earlier findings that readers show distinct reading profiles, or "strategies" [62][63][64]. According to the "Risky Reader Hypothesis" [59,60], more proactive, "risky readers", display long saccades and many regressions. They rely relatively strongly on guessing which words are in the parafovea, but often need to regress to an earlier word when this strategy fails.…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…This reading behavior is in line with earlier findings that readers show distinct reading profiles, or "strategies" [62][63][64]. According to the "Risky Reader Hypothesis" [59,60], more proactive, "risky readers", display long saccades and many regressions. They rely relatively strongly on guessing which words are in the parafovea, but often need to regress to an earlier word when this strategy fails.…”
Section: Figuresupporting
confidence: 90%
“…These results are in line with the theoretical considerations of Mukařovský [10] and Shklovsky [11]. If processing is too fluent, or automatic, there is little chance for appreciating the poetic dimension of the text (see [60,61]). Clearly, there is a limit to this: Very idiosyncratic language use can hinder the flow of information so much that it impairs comprehension.…”
Section: Figuresupporting
confidence: 86%
“…Accordingly, a recent study using proverbs has shown that (a) rhyme and meter can enhance perceived beauty, succinctness, and persuasiveness, while also reducing semantic processing ease (due to implementing constraints on both word choice and word order), and (b) the total sum of the contradictory effects on perceptual (phonological, prosodic) and conceptual (semantic) processing is still positive (cf. Menninghaus et al, 2015). We therefore emphasize that the positive correlation we found between patterns of phonological recurrence (rhyme and meter), ease of processing, and aesthetic liking of poetic stanzas does not amount to the hypothesis that the appreciation and enjoyment of poetry is all about reduced processing demands.Furthermore, conceptual fluency may be especially prone to individual differences, since problem-solving mechanisms rely on personal experiences of art, including knowledge of art history, cultural knowledge, and the contexts in which works of art are encountered.…”
Section: Ease Of Processing Is Enhanced By Poetic Language Usementioning
confidence: 61%
“…Specifically, Juslin suggests that "It is not that the of the concept of beauty throughout history [185]. More recently, empirical investigations have shown that perceived sadness and beauty tend to be highly correlated in such diverse stimuli as film music excerpts [194] and poems (where patterns of poetic diction have been manipulated; [195]). …”
Section: Aesthetic Appreciation and Beautymentioning
confidence: 99%